1995
DOI: 10.1172/jci117723
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-insulin-dependent diabetes mellitus on the kinetics of onset of insulin action in hepatic and extrahepatic tissues.

Abstract: The mechanism(s) of insulin resistance in non-insulin-dependent diabetes mellitus remains ill defined. The current studies sought to determine whether non-insulin-dependent diabetes mellitus is associated with (a) a delay in the rate of onset of insulin action, (b) impaired hepatic and extrahepatic kinetic responses to insulin, and (c) an alteration in the contribution of gluconeogenesis to hepatic glucose release. To answer these questions, glucose disappearance, glucose release, and the rate of incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 55 publications
3
21
1
Order By: Relevance
“…Increased gluconeogenesis is consistent with the current observation. Although gluconeogenesis has not been measured in the current study, increased glucose production and increased gluconeogenesis are reported to occur in type 2 diabetic patients when they are not treated (16). In the current study, the circulating amino acid concentrations remained unchanged, including alanine and glutamine.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Increased gluconeogenesis is consistent with the current observation. Although gluconeogenesis has not been measured in the current study, increased glucose production and increased gluconeogenesis are reported to occur in type 2 diabetic patients when they are not treated (16). In the current study, the circulating amino acid concentrations remained unchanged, including alanine and glutamine.…”
Section: Discussioncontrasting
confidence: 49%
“…It is possible that leucine oxidation may not truly reflect net urinary nitrogen loss in all physiological and pathological states (14,15). For example, there is an increased gluconeogenesis in type 2 diabetic subjects (16) when the circulating glucose levels are high, although their leucine flux is usually normal in this situation (7). Increased gluconeogenesis involves consumption of glucogenic amino acids that could theoretically increase urinary nitrogen loss.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1), responded differently to insulin than the muscle. During insulin infusion, the flux of substrates such as nonesterified fatty acids and amino acids decreases, thus reducing the overall liver substrate metabolism (48). However, replacement of amino acids alone failed to reverse the inhibitory effect of insulin on liver mitochondrial protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, replacement of amino acids alone failed to reverse the inhibitory effect of insulin on liver mitochondrial protein synthesis. Other potential factors that affect liver energetics include a suppression of gluconeogenesis in liver by insulin (48). At the postreceptor level, the insulin signaling pathway has been demonstrated to differ between the muscle and the liver.…”
Section: Discussionmentioning
confidence: 99%